A modified method for assessing sexual function in men - M. I. Yagubov; I. Yu. Kan; N. V. Dobaeva; I. R. Ayriyants (Лечащий Врач)
Background. Sexual disharmony is a significant factor in the destabilization of family relations, having a negative impact on the demographic situation. Disorders of sexual function often have comorbid associations with various somatic and mental illnesses, which determines the need for a comprehensive interdisciplinary approach to their diagnosis. However, doctors of various specialties often underestimate the importance of collecting anamnestic data on a patient's sexual health, which makes it difficult to detect such disorders early. In this regard, it is an urgent task to develop short screening tools that provide prompt diagnosis of sexual dysfunctions.Materials and methods. The study, conducted at the Department of Sexology at the Moscow Research Institute of Psychiatry, involved 194 men, 90 of whom had diagnosed sexual disorders, and 104 were in the control group. All the subjects were offered both classical and modified versions of the Male Sexual Function Assessment Scale.Results. Data analysis has demonstrated that the modified version of the Male Sexual Function Assessment Scale questionnaire is a highly reliable tool for detecting sexual dysfunctions in clinical practice and can be used for screening in order to refer patients to specialized specialists in a timely manner. The study confirmed that the shortened version of the scale has a high level of internal consistency (Cronbach α = 0.7629 after standardization), as well as a high diagnostic value, confirmed by ROC analysis (AUC = 0.889), which indicates its high sensitivity and specificity.Conclusion. The study found that the modified version of the Male Sexual Function Assessment Scale questionnaire demonstrates high reliability and diagnostic significance, which makes it an effective tool for use in clinical practice. The main advantages of the abridged version include: reduction of excessive detail of subjective aspects of sexual function, preservation of key diagnostic parameters, as well as increased usability by doctors of related specialties. This tool can be recommended for screening sexual dysfunctions in medical practice, which will allow timely detection of disorders affecting both the sexual and psychosomatic health of patients and refer them to appropriate specialists.